A compact multi-band notched characteristics UWB microstrip patch antenna with a single sheet of graphene - Noor Raheem; Nidal Qasem (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A rectangular tuneable Ultra-wideband (UWB) Microstrip Patch (MP) antenna based on a Single Sheet of Graphene (SSG) is designed in this study. The antenna band can be tuned by applying a DC voltage bias perpendicular to the SSG at various values via adjusting the input impedance. The antenna has been analyzed by Computer Simulation Technology (CST) Microwave Studio (MWS) software using an FR4 substrate of thickness 1.6 mm with a dielectric permittivity =4.4 and loss tangent tan =0.02 fed by a 50 Ω microstrip line frequency. The design is compact since the antenna consists mostly of copper and the SSG. Graphene’s low weight, high flexibility, and strength make it more attractive than other semiconductor materials. Then, the study investigates the effects of applying the electrical characteristics of graphene to the antenna’s length, which varies with the ON and OFF states. This UWB MP antenna is also designed with notch characteristics so that it can reject undesired interference signals. Subsequently, this compact UWB MP antenna with tuneable resonance frequency is suitable for most wireless communication applications. The simulation results work in the 3.1 to 10 GHz range, as required for UWB technology.